Transport and Charge Carrier Chemistry in Lithium Oxide. Issue 10 (1st January 2019) - Lorger, Simon; Usiskin, Robert; Maier, Joachim
Abstract : Lithium oxide (Li2 O) is a highly relevant material for battery applications, and as a binary antifluorite compound of first-row elements, it is equally interesting for basic science. This work investigates the behavior of ionic and electronic charge carriers in Li2 O. The predominantly ionic conductivity is shown to be well-explained by a defect chemical model based on Frenkel disorder, vacancy migration, and vacancy-dopant association. The enthalpies and entropies of these three processes are derived, and good agreement is seen to isostructural Li2 S, SrF2, and BaF2 . An upper bound is determined for the electronic conductivity of Li2 O, which is very low. These results provide more reliable thermodynamic and kinetic parameters for future rigorous treatments of Li2 O in batteries. For example, even under favorable doping conditions, the ionic conductivity of bulk crystalline Li2 O (with no higher-dimensional defects or interfacial effects) is multiple orders of magnitude too slow to account for the resistance of typical solid-electrolyte interface (SEI) layers.